The firms' integration process of the twin pillars of environmental sustainability: Climate change and biodiversity loss - Fredrik N. G. Andersson; Susanne Arvidsson (Lund University, School of Economics and Management, Department of Economics, 2024)
This study examines the integration of climate change and biodiversity into business strategies and governance structures of listed firms on the Swedish stock exchange NasdaqOMX Large Cap. The results show clear disparities in the level of integration and the factors driving the integration process. All, but a few small firms, have integrated climate change into business strategies, and are ahead in the process of integrating it into governance structures. Biodiversity integration is lagging behind the integration of climate change. We also find that the integration process depends on the sustainability competences within the board unlike climate change when the board composition is less important. Additionally, our results show that firms require external pressures from, e.g., regulations to integrate biodiversity and climate change into business strategies and governance structures.
Keywords: 330; biodiversity; climate change; sustainable finance; business strategy; governance structures; CSRD